Pseudomyxoma Peritonei Mimicking Liver Cirrhosis: A Case Report and Literature Review - Diah Pradnya Paramita; Gde Somayana (The Indonesian Society for Digestive Endoscopy, 2026)
Pseudomyxoma peritonei (PMP) is a rare condition caused by rupture of a primary mucinous tumor, followed by dissemination of tumor cells within the peritoneal cavity and excessive mucin production. The signs and symptoms are generally nonspecific, making early diagnosis difficult. We present a man, age 57, who showed abdominal distention accompanied by nausea and vomiting for approximately four months, which was referred to as liver cirrhosis. Carcinoembryonic antigen level was elevated and postoperative histology revealed low-grade peritoneal mucinous neoplasia. The signs and symptoms of PMP are generally nonspecific, making it difficult to diagnose earlier and leading to delayed appropriate treatment. Computed tomography (CT) scan is the preferred imaging modality for determining the extent of the disease preoperatively. Elevated tumor marker level, especially CEA, CA19-9, and CA-125, is usually suggestive of the diagnosis of PMP. Immunohistochemistry was used to determine the origin of primary malignancy. PMP management needs to be individualized; therefore, discussion among multidisciplinary teams is needed. Currently, the most common treatment option is cytoreductive surgery (CRS) in conjunction with hyperthermic intraperitoneal chemotherapy (HIPEC) and has been associated with improved survival in several studies. However, if there are limitations in therapeutic modalities or patient populations, alternative therapies can be used. This case report aims to highlight the diagnostic challenges of pseudomyxoma peritonei presenting as ascites that mimics liver cirrhosis.